The Relationship between Mental Health and Obedience to Worship in Adolescent Boys : Irda Eviriani, Lutiyah, Hadi Abdillah, Ernawati Hamidah - Irda Eviriani; Lutiyah; Hadi Abdillah; Ernawati Hamidah (PROFESSIONAL HEALTH JOURNAL, 2025)
Obedience in worship is considered as one of the factors that can affect mental health. This study aims to determine the relationship between mental health and obedience to worship in adolescent boys. The population in this study were 104 adolescent boys from the Faculty of Health, University of Muhammadiyah Sukabumi. The sample in this study was 50 male adolescents aged 12-21 years at the Faculty of Health. The research was conducted at the Faculty of Health, Universitas Muhammadiyah Sukabumi. Data collection techniques in this study using questionnaire research instruments. Data analysis techniques used were univariate analysis and bivariate analysis. The results of the P value obtained from the Chi Square test for asymp sig. (2-sided) is 0.000. This value shows the result of p <0.05. So it can be concluded that there is a significant relationship between mental health and obedience to worship in adolescent boys.